Role of short term Video EEG monitoring and MRI in refractory Epilepsy - Kumari, D.V. Madhavi; Kumari, Aruna; Kumar, Sateesh; Seepana, Gopi; Raju, G. Butchi (Nepal Journal of Neuroscience, 2023)
Introduction: Inpatient video EEG monitoring is widely used for the diagnosis, seizure classification and pre surgical evaluation of patients with epilepsy. Only few studies have highlighted the role of short term video EEG in the diagnosis of paroxysmal events. The present study was undertaken to identify the role of short term video EEG in refractory epilepsy.Materials & Methods: Forty patients, attending neurology outpatient department in our institution, during the study period, fulfilling the criteria for refractory epilepsy were included. Short term video EEG and MRI Brain were done for all of them. Outcomes measured were 1) Video recording of epileptic seizures with concurrent ictal pattern or psychogenic non epileptic seizure. 2) Identification of new interictal epileptiform discharges, which were not there in the previous routine EEG. 3) Observation of congruency between EEG and MRI Brain.Results: Clinical events were recorded in 12.5% of patients - 7.5% had epileptic seizures and 5% had psychogenic non epileptic seizures recorded. Short term video EEG was abnormal in 70% of the patients, whereas previous routine EEG was abnormal in only 30% and these observations were statistically significant. Short term video EEG was useful in diagnostic classification in 70% of the cases. MRI Brain was abnormal in 35% and among them, 30% had lateralized epiletiform discharges and the congruency between them is not statistically significant.Conclusions: Short term video EEG monitoring could be an initial investigation to sort our more frequent seizure group and proceed to long term VEEG if short term VEEG is inconclusive.